Analisa Akuntabilitas Belanja Hibah pada Pemerintah Kota Manado - Runtuwarouw, Margaretha Yeane; Ilat, Ventje; Lambey, Linda (Universitas Sam Ratulangi, 2019)
Abstract. This study aims to analyze the accountability of grant expenditure on the Government of the City of Manado. This research is a qualitative research with an exploratory approach. Data were obtained by in-depth interviews and documentation study. It was concluded that there are obstacles in the six grant expenditure management processes. The problems have occurred in the processes of accountability and reporting. Those problems are (1) compliance problems occurred in the process of implementing grants expenditure accountability, (2) regulatory constraints in which regulations have not yet been conveyed to grant managers, especially in relation to regional equipment, (3) constrains in the implementation of grant spendings in which they are processed in longer time because they have to go through several stages, (4) constraints in terms of lack of human resources competencies and capabilities of accountability and reporting, and (5) the limitations of supporting facilities in realizing accountability for grant spending. This study found that the coordination among grants managers, information and communication both managers and recipients of grants are very important to achieve accountability. Socialising regulations related to grant spending, affirming sanctions and aiding community or grant recipients will help to achieve better grant expenditure accountability. Various efforts were made to minimize the delay in submitting the grant fund accountability report, namely by giving sanctions, coordination between grant managers, more intensive requests for reports from recipients of the grant as well as the formulation of a standardized accountability report format to allow Â grantees to compile accountability reports easier and to ease reviewers to examine the reports.Keywords: Grants Expenditure Accountability, Local Government.Abstrak. Penelitian ini bertujuan untuk menganalisa akuntabilitas belanja hibah pada Pemerintah Kota Manado. Penelitian ini adalah penelitian kualitatif dengan pendekatan eksploratori. Data diperoleh dengan teknik wawancara mendalam dan studi dokumentasi. Disimpulkan bahwa dari keenam proses pengelolaan belanja hibah, terdapat proses yang sering mengalami kendala yaitu proses pertanggungjawaban dan pelaporan. Kendala-kendala tersebut adalah (1) kendala kepatuhan yang terjadi dalam proses pelaksanaan akuntabilitas belanja hibah, (2) kendala regulasi, dimana regulasi belum tersampaikan kepada pengelola hibah khususnya perangkat daerah terkait, (3) kendala pelaksanaan belanja hibah yakni proses yang memerlukan waktu agak lama karena harus melewati beberapa tahap, (4) kendala kompetensi sumberdaya manusia dalam proses pertanggungjawaban dan pelaporan, (5) serta keterbatasan fasilitas penunjang merupakan kendala-kendala dalam mewujudkan akuntabilitas belanja hibah. Disamping itu, kerjasama antara pengelola hibah, informasi dan komunikasi baik untuk pengelola maupun penerima hibah sangat diperlukan dalam pencapaian akuntabilitas. Pentingnya sosialisasi peraturan-peraturan terkait belanja hibah, penegasan sanksi serta pendampingan bagi masyarakat atau penerima hibah akan membantu terlaksananya akuntabilitas belanja hibah yang lebih baik. Berbagai upaya dilakukan untuk meminimalisasikan keterlambatan penyampaian laporan pertanggungjawaban dana hibah yaitu dengan pemberian sanksi, adanya koordinasi antara pengelola hibah, permintaan laporan kepada penerima hibah yang lebih intensif serta penyusunan format laporan pertanggungjawaban yang baku agar memudahkan penerima hibah menyusun laporan pertanggungjawaban dan memudahkan pemeriksa.Kata kunci : Akuntabilitas Belanja Hibah, Pemerintah Kota.